2014
DOI: 10.1002/prot.24700
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate binding module recognition of xyloglucan defined by polar contacts with branching xyloses and CH‐Π interactions

Abstract: Engineering of novel carbohydrate-binding proteins that can be utilized in various biochemical and biotechnical applications would benefit from a deeper understanding of the biochemical interactions that determine protein-carbohydrate specificity. In an effort to understand further the basis for specificity we present the crystal structure of the multi-specific carbohydrate-binding module (CBM) X-2 L110F bound to a branched oligomer of xyloglucan (XXXG). X-2 L110F is an engineered CBM that can recognize xylogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…These results suggest the relevance for these interactions on the substrate specificity of CBMs. 128 Recently, the neutron structure of the same mutant, specifically X-2 L110F derived from CBM4-2 from the R. marinus xylanase, was reported, 129 providing the first CBM structure define using this technique and making it possible to demonstrate the importance of water molecules in hydrogen bonding in CBM-ligand interactions, a previously questioned issue. It is known that both the parental CBM X-2 and its X-2 L110F mutant contain ordered water molecules at the binding site and that at least 10 of these molecules are displaced by the union with a carbohydrate, although three of these molecules remain at the binding site.…”
Section: Methods For Selecting and Displaying Engineered Cbm Variantsmentioning
confidence: 99%
“…These results suggest the relevance for these interactions on the substrate specificity of CBMs. 128 Recently, the neutron structure of the same mutant, specifically X-2 L110F derived from CBM4-2 from the R. marinus xylanase, was reported, 129 providing the first CBM structure define using this technique and making it possible to demonstrate the importance of water molecules in hydrogen bonding in CBM-ligand interactions, a previously questioned issue. It is known that both the parental CBM X-2 and its X-2 L110F mutant contain ordered water molecules at the binding site and that at least 10 of these molecules are displaced by the union with a carbohydrate, although three of these molecules remain at the binding site.…”
Section: Methods For Selecting and Displaying Engineered Cbm Variantsmentioning
confidence: 99%
“…At 1.0 Å resolution we were able to observe unassigned F o À F c density corresponding to some H atoms in the protein, in the ligand and on a few well ordered water molecules. However, the data were not strong enough to support the modelling of explicit positions for H atoms (von Schantz, Hå kansson et al, 2014;von Schantz et al, 2012). From these previous ultra high-resolution X-ray crystallographic studies, many details of carbohydrate binding were observed.…”
Section: Introductionmentioning
confidence: 90%
“…X-2 is specific for xylan (and its synthetic mimic oligoxylose). Further mutagenesis identified the single mutant X-2 L110F (von Schantz et al, 2012) that, similar to the wild-type module, is able to bind multiple carbohydrates including not only xylan but also -glucan and xyloglucan (von Schantz, Hå kansson et al, 2014;von Schantz et al, 2012). In both CBM variants residue 110 stacks against the ligand in the cavity of the CBM ligand-binding site (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This wedgeshaped structure is likely to be shared by all fungal CBDs (Mattinen et al 1997). The specificity of CBMs can be changed through simple mutations (von Schantz et al 2014). It was suggested that tryptophan residues contribute to higher binding affinity than tyrosine residues.…”
Section: Fundamentals Of Cellulose Binding Domainsmentioning
confidence: 99%